Building the IPO order book: underpricing and participation limits with costly information - Sherman, Ann E.; Titman, Sheridan (Journal of Financial Economics, 2002)
We examine the book-building method for marketing IPOs. In our model, the underwriter selects a group of investors along with a pricing and allocation mechanism to maximize (at minimum cost) the information generated during the process of going public. We also address the moral hazard problem faced by investors when evaluation is costly. When there is little need for accurate pricing, the expected gain from underpricing exactly offsets the investors’ costs of acquiring information. When pricing accuracy is important, however, the number of investors participating in the offering is larger, underpricing is greater, and investors can earn economic rents.